Relationship between climatic factors and the flea index of two plague hosts in Xilingol League, Inner Mongolia Autonomous Region - Lu Zhang; Zihao Wang; Nan Chang; Meng Shang; Xiaohui Wei; Ke Li; Jinyu Li; Xinchang Lun; Haoqiang Ji; Qiyong Liu (Elsevier, 2024)
Climatic factors are closely associated with the occurrence of vector-borne diseases, and they also influence the distribution of vectors. The occurrence of plague is closely related to the population dynamics of fleas and their host animals, as well as climatic conditions. This study focused on Xilingol League, utilizing climatic and flea index data from 2012 to 2021. Spearman correlation and ''Boruta'' importance analysis were conducted to screen for climatic variables. A generalized additive model (GAM) was employed to investigate the influence of climatic factors and rodent density on the flea index. GAM analysis revealed distinct trends in flea index among different rodent hosts. For Meriones unguiculatus, the flea index declined with increased density and with higher humidity, yet rose with greater lagged sunshine duration. For Spermophilus dauricus, an initial increase in flea index with density was observed, followed by a decrease, and a rise in the index was noted when ground temperatures were low. This study reveals the nonlinear interactions and lag effects among climatic factors, density, and flea index. Climatic factors and density variably influence the flea index of two Yersinia pestis hosts. This research advances the prediction and early warning efforts for plague control, providing a theoretical basis for rodent and flea eradication strategies.